Assessment of Altered Cholesterol Homeostasis by Xenobiotics Using Ultra‐High Performance Liquid Chromatography–Tandem Mass Spectrometry. Issue 1 (15th October 2018) - Herron, Josi; Hines, Kelly M.; Xu, Libin
Abstract: Cholesterol and cholesterol‐derived oxysterols are critical for embryonic development, synapse formation and function, and myelination, among other biological functions. Indeed, alterations in levels of cholesterol, sterol precursors, and oxysterols result in a variety of developmental disorders, emphasizing the importance of cholesterol homeostasis. The ability of xenobiotics to reproduce similar phenotypes by altering cholesterol homeostasis has increasingly become of interest. Therefore, the ability to quantitatively assess alterations in cholesterol homeostasis resulting from exposure to xenobiotics is of value. This unit describes methods for the quantitative assessment of altered post‐squalene cholesterol biosynthesis and subsequent oxysterol formation in various sample types using ultra‐high performance liquid chromatography‐tandem mass spectrometry (UHPLC‐MS/MS). Understanding alterations in cholesterol homeostasis resulting from xenobiotic exposure can provide key insight into the toxicant's mechanism of action and resulting phenotype. © 2018 by John Wiley & Sons, Inc.